Hope in hell inside the world of Doctors Without Borders - Bortolotti, Dan (A Firefly book, 2004)
Account of the experiences of individual medical professionals who work for Doctors without Borders around the world, including Africa, Asia and Europe. Covers how Doctors without Borders was founded and how the organization has reacted to recent world events.